PENANGANAN FIBROMA PADA RONGGA MULUT - Dermawan, IGN Putra; Suparka, Made Merta (Interdental: Jurnal Kedokteran Gigi, 2020)
The fibroma is an abnormal growth of tissue in the form of a hyperplasia reaction of the fibrous connective tissue that could be induced by irritation or local trauma to the oral cavity. Clinically this tumor is similar to other connective tissue lesions. A 42-year-old housewife came to RSGM FKG Mahasaraswati University Denpasar with a complaint of feeling uncomfortable on her left cheek and a lump since 4 months ago due to frequent bites. Intraoral examination revealed a prominent lesion on the left cheek of 1.2 cm. The patient was referred for Oral Surgery and surgery and suturing were performed. Within 1 week the lesions were healed. After taking anamnesis, clinical examination, and support, the disorder was diagnosed as Traumatic Fibroma.